Análise do processo de implantação da rede de atenção às urgências e emergências na região metropolitana de Fortaleza ampliada - Ceará - Teixeira, Juliana Maria Cavalcante (2014)
In Brazil, the old fragmented model of public healthcare is being gradually replaced by a network model, based on evidence that networks represent a feasible solution to the current crisis in primary care. Albeit insufficient to meet the needs and expectations of the population, recently issued government directives determining the reordering of the current urgency and emergency healthcare system into network format have led to improvements by introducing a design compatible with the reality of the demand. The purpose of this study was to analyze the implementation of a network of urgency and emergency healthcare (RUE) in Greater Fortaleza (a state capital in Northeastern Brazil), correlating the observed practices with the Ceará State Action Plan and identifying factors favoring or hampering the process. Adopting a qualitative approach, we collected information through a review of pertinent legal literature and interviews with municipal authorities and RUE managers. The data were submitted to desk study and thematic analysis. Our findings revealed poor integration between the components of the RUE. The associated factors included insufficiency of primary care and management fragmentation evidenced by the absence of unified network governance. In addition, the drafting of the Ceará State Action Plan did not adequately anticipate the bottlenecks of public healthcare and of RUE implementation in all its aspects. In conclusion, despite considerable political and financial investment, implementation strategies have been unable to circumvent the lack of integration between health services. Furthermore, implementation has been compromised by the low priority given to primary care (on which urgency and emergency care depends), funding trammels and limitations in the communication between municipal authorities and RUE managers. In other words, the emphasis placed on urgency and emergency care has so far contributed little to the development of healthcare networks and the reordering of the Brazilian primary healthcare system.